Let's talk 1 / Leo Jones - Leo, Jones
Let's talk is about communication. It is about listening to and understanding other people's ideas, and about sharing your ideas with your fellow students. Be brave! Mistakes are an important part of learning. You will make progress, even if you sometimes make a mistake. Your partners and teacher will correct the mistakes that prevent you from communicating effectively.